1990
DOI: 10.1038/bjc.1990.84
|View full text |Cite
|
Sign up to set email alerts
|

Origin of marrow stromal cells and haemopoietic chimaerism following bone marrow transplantation determined by in situ hybridisation

Abstract: Summary The origin and cell lineage of stromal cells in the bone marrow is uncertain. Whether a common stem cell exists for both haemopoietic and stromal cells or whether these cell lines arise from distinct stem cells is unknown. Using in situ hybridisation for detection of the Y chromosome, we have examined histological sections of bone marrow from seven patients who received marrow transplants from HLA-matched donors of the opposite sex. Stromal cells (adipocytes, fibroblasts, endothelial cells, osteoblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…So far, endothelial cell chimerism has not been analyzed after ABO-incompatible HSCT, but it has been described after gender-mismatched HSCT. Two earlier studies, which did not find donor-type endothelial cells in the stromal constituents of bone marrow up to 3 years after HSCT, 29,30 were contrasted by several reports showing endothelial cell chimerism in skin, gut, heart and bone marrow after gender-mismatched HSCT. [14][15][16][17][18]31,32 All these studies used XY in situ hybridization for the detection of donor-derived cells.…”
Section: Discussionmentioning
confidence: 65%
“…So far, endothelial cell chimerism has not been analyzed after ABO-incompatible HSCT, but it has been described after gender-mismatched HSCT. Two earlier studies, which did not find donor-type endothelial cells in the stromal constituents of bone marrow up to 3 years after HSCT, 29,30 were contrasted by several reports showing endothelial cell chimerism in skin, gut, heart and bone marrow after gender-mismatched HSCT. [14][15][16][17][18]31,32 All these studies used XY in situ hybridization for the detection of donor-derived cells.…”
Section: Discussionmentioning
confidence: 65%
“…Some controversy exists in the literature as to whether stromal elements contribute to donor chimerism after an allogeneic transplant in patients (19,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In this study, we did not analyze stromal donor contribution, but rather focused on the stromal progenitors, the MSC, which were isolated and expanded according to Caplan et al (9,(40)(41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%
“…Also, after implantation in chambers with porous membranes or on ceramic cubes, the cells form fibrous tissue, cartilage, and bone in vivo. Some reports (19)(20)(21)(22)(23)(24) suggested that MSCs do not engraft in marrow after systemic infusion, but other reports described successful marrow engraftment (2,(25)(26)(27)(28)(29)(30). Many of the negative experiments may be explained by species differences in the animal models, the conditions used for marrow ablation, the number of cells infused, the protocols used to prepare the cells, or the markers used to identify the donor cells (10).…”
mentioning
confidence: 99%